CHANGE OF TEMPERATURE AND DISSOLVED OXYGEN CONTENTS IN THE PRODUCTION OF SLURRY ICE COMBINED WITH NITROGEN NANO - Hung, Dinh Xuan; Cuong, Truong Quoc (HUIT Journal of Science, 2024)
The combination research of slurry ice technology and Nitrogen Nanotechnology was implemented in order to create a new slurry ice solution of temperature from -1 oC to -2 oC and dissolved oxygen content of under 1,0 mg/L. There were four experiment, including: (1) Turning on the Nitrogen Nano machine to reduce the DO content in the water to less than 1.0 mg/L and then stopping it before turning on the slurry ice machine (CDH1); (2) Two machines operate simultaneously (CDH2); (3) Two machines start simultaneously and when the temperature of the water reaches to 0 oC, stop Nitrogen Nano machine priorly (CDH3); and (4) The slurry ice machine works until temperature of the solution reaches 0 oC, Nitrogen Nano machine starts running (CDH4) and one control experiment (NoNano). The results indicated that setting up for the Nitrogen Nano and slurry ice machines operates simultaneously (CDH2) or Nitrogen Nano machine is timed for running when the temperature of the mixture reached 0 oC (CDH4), that attained both DO content and temperature at the end of the process was less than 1.0 mg/L and -1.5 oC respectively. In concern about both economy and technology aspects, recommending while slurry ice working, Nitrogen Nano machine is timed for running when the mixture reaches temperature of 0oC then both machines operate to end of process.